Love Heart / Siti Nurul Hija Ishak ... [et al.] - Ishak, Siti Nurul Hija; Mohd Kamal, Nahzatul Faiza; Zolkpli, Siti Yuhaini; Kassim, Naemah (Faculty of Civil Engineering, 2003)
In line with "all about loves... " concept, Love Heart is committed to provide all of our clients with a consistent quality of services to give them the technical and management support required to remain competitive. Love heart is involved in supplying and manufacturing flowers.